Atherosclerosis in chronic organic arsenic (monosodium methylarsonate) exposure - Abdullah, Nor Zamzila; Ishola, Afeez Adekunle; A.Talib, Norlelawati; Muhammad, Siti Aeshah @ Naznin; Buyong, Zunariah; Myint, Yi Yi; Mohamed, Abdul Hadi; Samsuddin, Niza; Abdul Ghani, Radiah (College of Pathologists, Academy of Medicine Malaysia, 2015)
Human worldwide are exposed to arsenic mainly through drinking of arsenic-contaminated ground water. Arsenic is one of the environmental toxins reported to be associated with atherosclerosis with more attention given to inorganic arsenic as it was thought to be more toxic. Since organic arsenic particularly monosodium methylarsonate are still popularly being used and produced for agricultural activities, this study aimed to investigate the effects of chronic organic-arsenic exposure on the development of atherosclerosis in a rat model based on real human exposure. Materials & Methods: Fifty five male Sprague-Dawley rats were divided into 5 groups including a control group. Four treatment groups received oral intubation of monosodium-methylarsonate (MSMA) at 42.13, 63.30, 126.4 and 210.67 mg/kg body weight respectively every day for 16 weeks. Aorta were harvested and stained for H&E and Verhoef Van Gieson as well as for immunohistochemistry VCAM-1 and ICAM-1. Results: Rats treated with 126.4 and 210.67 mg/Kg BW of MSMA was noted to have high mortality due to severe diarrhea and drastic weight reduction and therefore was discontinued from our study. Rats treated with 42.13 and 63.3 mg/Kg BW MSMA showed positive early atherosclerosis changes microscopically with positive VCAM-1 and ICAM-1 expression. Discussion: This study highlighted that chronic organic arsenic exposure with MSMA also leads to the development of atherosclerosis. This indicates that chronic organic arsenic exposure is as equally toxic as inorganic arsenic exposure in the development of atherosclerosis.